Evaluation of Arbuscular Mycorrhizal Cultures in Increasing Phosphorus Uptake and Maize Growth Compared to Chemical and Organic Fertilizers on an Andisol - Cahyani, Vita Ratri; Azzahra, Nadine Yuki; Rosariastuti, Retno (AGRIVITA Journal of Agricultural Science, 2024)
There is still limited information about the formulation of arbuscular mycorrhizal (AM) fungi culture with the specific ability to overcome P retention in Andisols. The purpose of this study is to evaluate the functional ability of eight AM fungi cultures consisting of four cultures from the generation I (A1I31, A2I21, A0I31, and A0I21) and four cultures from generation II (A1I32, A2I22, A0I32, and A0I22) in dealing with P constraints on an Andisol, compared with the application of fresh AM fungi inocula isolated from natural soils, synthetic chemical fertilizers (CF), rice straw (RS) compost, and several combination treatments including Bio-RP Nutrition. The highest functional ability in increasing P uptake and maize growth on Andisol is obtained by A1I32, followed by A2I22 and A0I22, indicating that AM fungi cultures generation II exhibited higher effectiveness than generation I. The increase of P uptake and maize shoot dry weight yielded by those three AM fungi cultures were in the range of 80-97% and 89-103% of T14 (CF 100%), indicating the high potential biofertilizers for reducing the use of chemical fertilizers. By  cultivation  plate  method,  the  present  findings  also  confirmed that  AM   fungi   inoculation   affecting  significantly   the   abundance and  the  composition  of  foliar  endophytic  bacterial  communities.